The inland fisheries with special reference to Temengor and Bersia reservoirs, Perak - Hamid, M.A.; Mansor, M. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Temengor and Bersia reservoirs which were constructed mainly for the purpose of hydropower generation and flood mitigation have contributed towards the inland fisheries of Malaysia. However, the contribution towards the total fish landings from these reservoirs is poorly documented. Hence, a study on inland fisheries has been conducted in two consecutive reservoirs along Sungai Perak. A monthly study on fish diversity and distribution at these two reservoirs had been carried out for ten months between August 2009 and December 2010. A total of 20 species, which comprised of eight families, was recorded during this study. Cyprinidae was the most dominant family in terms of the number caught in Temengor and Bersia reservoirs with 94% and 78%, respectively while the other families were only represented by one or two species. Nineteen species were recorded in Temengor whereas 16 species were recorded in Bersia. Shannon-Wiener diversity and evenness indices were higher in Bersia Reservoir (2.030; 0.732) as compared to Temengor Reservoir (1.921; 0.653). In particular, total catch in both lakes showed that Osteochilus vittatus and Cyclocheilichthys apogon were two dominant species caught during this study. Based on Mann-Whitney U Test, there is no significant difference (p>0.05) between the total individual number per species caught in Temengor and Bersia reservoirs. Therefore, Temengor Dam does not affect the fish abundance of Bersia Reservoir.